2020
DOI: 10.1002/que2.30
|View full text |Cite
|
Sign up to set email alerts
|

Correlation measure equivalence in dynamic causal structures of quantum gravity

Abstract: Summary We prove an equivalence transformation between the correlation measure functions of the causally unbiased quantum gravity space and the causally biased standard space. The theory of quantum gravity fuses the dynamic (nonfixed) causal structure of general relativity and the quantum uncertainty of quantum mechanics. In a quantum gravity space, the events are causally nonseparable and all time bias vanishes, which make it no possible to use the standard causally biased entropy and the correlation measure … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 77 publications
0
10
0
Order By: Relevance
“…Intrestingly, in Ref. [13], the author present the quantum correlation measure equivalence in dynamic causal structures of quantum gravity, which maybe helpful for investigating the quantification of coherence. Coherence in multipartite systems has been also studied [14][15][16], together with its relations to quantum entanglement and quantum nonlocality [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Intrestingly, in Ref. [13], the author present the quantum correlation measure equivalence in dynamic causal structures of quantum gravity, which maybe helpful for investigating the quantification of coherence. Coherence in multipartite systems has been also studied [14][15][16], together with its relations to quantum entanglement and quantum nonlocality [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, much attention has been paid to the resource theory of coherence [1][2][3][4][5][6][7][8][9][10], entanglement [11], asymmetry [12][13][14][15] and nonuniformity [16,17]. As a fundamental feature of quantum physics, quantum coherence plays significant roles in quantum metrology [18,19], low-temperature thermodynamics [20][21][22][23][24], nanoscale physics [25][26][27][28][29][30], and quantum measurement [31][32][33]. The quantification of quantum coherence of quantum states has been extensively investigated, see [34][35][36][37] and references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding quantum effects in the framework of relativity [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] is essential. For example, it was found that nonclassical correlations are generated between the open charts in the exponentially expanding de Sitter space [36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%